Collagen Fibril Ultrastructure in Mice Lacking Discoidin Domain Receptor 1. (22nd June 2016) - Tonniges, Jeffrey R.; Albert, Benjamin; Calomeni, Edward P.; Roy, Shuvro; Lee, Joan; Mo, Xiaokui; Cole, Susan E.; Agarwal, Gunjan
Abstract: The quantity and quality of collagen fibrils in the extracellular matrix (ECM) have a pivotal role in dictating biological processes. Several collagen-binding proteins (CBPs) are known to modulate collagen deposition and fibril diameter. However, limited studies exist on alterations in the fibril ultrastructure by CBPs. In this study, we elucidate how the collagen receptor, discoidin domain receptor 1 (DDR1) regulates the collagen content and ultrastructure in the adventitia of DDR1 knock-out (KO) mice. DDR1 KO mice exhibit increased collagen deposition as observed using Masson's trichrome. Collagen ultrastructure was evaluated in situ using transmission electron microscopy, scanning electron microscopy, and atomic force microscopy. Although the mean fibril diameter was not significantly different, DDR1 KO mice had a higher percentage of fibrils with larger diameter compared with their wild-type littermates. No significant differences were observed in the length of D-periods. In addition, collagen fibrils from DDR1 KO mice exhibited a small, but statistically significant, increase in the depth of the fibril D-periods. Consistent with these observations, a reduction in the depth of D-periods was observed in collagen fibrils reconstituted with recombinant DDR1-Fc. Our results elucidate how DDR1 modulates collagen fibril ultrastructure in vivo, which may have important consequences in the functional role(s) of the underlying ECM.